Comparative genomics analysis of the multidrug-resistant Aeromonas hydrophila MX16A providing insights into antibiotic resistance genes - Guo, Yuxin; Zeng, Chenxi; Ma, Chenjie; Cai, Hongjiao; Jiang, Xinglong; Zhai, Shaowei; Xu, Xiaojin; Lin, Mao (Frontiers in Cellular and Infection Microbiology, 2022)
In this paper, the whole genome of the multi-drug resistant pathogen Aeromonas hydrophila MX16A is reported with the genome sequenced using a PacBio single molecule real time whole genome sequencing technology. To shed light on the antibacterial mechanism of A. hydrophila MX16A, a Kirby-Bauer disk diffusion method was used to assess the phenotypic drug susceptibility of A. hydrophila. Importantly, drug resistance against β-lactam, sulfonamides, rifamycins, macrolides, tetracyclines and chloramphenicols was largely consistent with the prediction analysis results of drug resistance genes in the CARD database. The varied types and distributions of antibiotic genes identified from A. hydrophila MX16A revealed multiple resistance mechanisms, including enzyme inactivation, gene mutation and active effusion. The MX16A genome was compared with the published 35 strains of A. hydrophila genome downloaded from the NCBI database. The analysis of 33 genomes with ANI greater than 95% showed that the pan-genome consisted of 9556 genes, and the core genes converged to 3485 genes. In summary, the obtained results showed that A. hydrophila exhibited a large genomic diversity as well as diverse metabolic function and it is believed that frequent exchanges between strains lead to the horizontal spread of drug resistance genes.